Inhibitory Effects of Linot, Yellow, and Black Honey Extracts on Carbapenem-Resistant Klebsiella pneumoniae and Escherichia coli in Wound Infections - Ramadhan Willy Saputra; Mirnasari Amirsyah; Mudatsir; Wilda Mahdani; Syamsul Rizal (Gema Lingkungan Kesehatan, 2024)
Honey is known to have potential as an alternative treatment for wound infections caused by bacteria. This study aimed to evaluate honey's antimicrobial activity against Carbapenem-resistant Klebsiella pneumoniae and Escherichia coli in vitro. Methodology: The antibacterial activity test of honey was conducted using the disc diffusion method. The data were analyzed using one-way ANOVA and post-hoc tests. The results showed that the ethyl acetate fraction of Linot honey exhibited the highest inhibition zones against Carbapenem-Resistant Klebsiella pneumoniae and Escherichia coli; 25.64±0.20 mm and 25.07±0.05 mm, respectively. This study indicates that the ethyl acetate fraction of Linot honey possesses high antibacterial activity against these bacteria in vitro. Conclusion: This research supports using Linot honey as an alternative treatment for skin infections caused by Klebsiella pneumoniae and Escherichia coli.